PROGRAM LUMBUNG PANGAN (FOOD ESTATE) DI HUTAN INDONESIA MENURUT PARIS AGREEMENT - Anfasa Isyam Derawan; Arlina Permanasari (Faculty of Law, Universitas Trisakti, 2023)
The Food and Agriculture Organization (FAO) thinks there will be a national food security crisis due to the Covid-19 pandemic. The Food Estate Program (FEP) is Indonesia's answer to this problem. The FEP uses vast forest lands and this will threaten Indonesia's contribution to climate change. Such programs can lead to deforestation. Indonesia's contribution in this regard is in two sectors, namely adaptation and mitigation. In the mitigation sector, forests are the main weapon in curbing climate change. Indonesia can violate the Paris Agreement where Indonesia has ratified the international agreement. The problem in this article is whether the forest utilization program as a Food Estate is in accordance with the NDC in the Paris Agreement? The method used in this article is a normative and descriptive legal research method, using secondary data and secondary legal materials, as well as using library research in collecting data. The results of the research, discussion and conclusions from this article are that the forest utilization program as a Food Estate is not in accordance with the NDC as stipulated in the Paris Agreement because it will have an impact on not fulfilling Indonesia's obligations to make a positive contribution to climate change.